Striking the balance : women, men, work and family : discussion paper 2005 - Goward, Pru.; Australia. Human Rights and Equal Opportunity Commission. Sex Discrimination Unit. (Sydney : Sex Discrimination Unit, Human Rights and Equal Opportunity Commission, 2005)
"This paper aims to stimulate and contribute to public debate on current practices and attitudes among Australian men and women and the policies that help shape those practices and attitudes. An examination of caring and domestic arrangements in the home will assist better understanding of the gender relations which structure the paid work and family debate. In doing so, it will attempt to draw links between the "public" realm of the paid workforce and the "private" realm of the household."--p. 7.
"Submissions are invited on the issues raised ... Closing date for submissions: 30 September 2005"--p. iii.
Authors: Pru Goward ... [et al]
Includes bibliographical references.
Also available in an electronic version on the Internet. Address as of 08/02/06: http://www.hreoc.gov.au/sex_discrimination/strikingbalance
System requirements: Adobe Acrobat Reader required to view/print PDF files.
Keywords: Work and family -- Australia; Families -- Time management -- Australia; Part-time employment -- Australia; Quality of life -- Australia